Efficacy of cascade plasmapheresis in comparison with conventional therapeutic plasma exchange for relapsed atypical hemolytic uremic syndrome: A case report - Ashwinkumar Vaidya; Isha Polavarapu; Ravindra Attur Prabhu; Ganesh Mohan; Shamee Shastry; P A Prethika (Asian Journal of Transfusion Science, 2022)
Atypical hemolytic uremic syndrome (aHUS) is a rare and life-threatening disease that is associated with high mortality and morbidity. The incidence of aHUS is about 1 or 2 cases per 1,000,000 per year. Etiology can be either familial or sporadic. The pathogenesis of aHUS involves dysregulation of the alternative complement pathway, with predisposing mutations in complement genes. aHUS has a poor prognosis and a gradual or a relapsing (30%–86%) clinical course. The disease may present at any age but is mostly seen in children and young adults. Therapeutic plasma exchange (TPE) is one of the primary modalities of treatment in aHUS. This report presents the utilization of cascade plasmapheresis and its advantages over TPE in a patient with relapsed aHUS. There was a 73% decrement in antifactor H antibody levels following cascade plasmapheresis.